The association between inclusive leadership and pro-social rule breaking: Gender as moderator - Purwaningtias, Gina; Purba, Debora Eflina (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study explores the relationship between inclusive leadership and pro-social rule breaking (PSRB), with gender as a moderating factor. Drawing on role theory, it posits that women and men may exhibit different behaviors in work contexts. While women are typically linked with communal, socially oriented behaviors, men tend to show agentic, achievement-focused behaviors. This difference may influence how men and women respond to inclusive leadership in the workplace, including their likelihood of engaging in PSRB. Methods: The study involved employees from hospitality companies in Indonesia (N=193). Data were collected through an online survey, and the relationships were analyzed using Hayes' PROCESS macro on SPSS software. Findings: Inclusive leadership was found to have a negative correlation with PSRB. Gender moderated this relationship, with a significant negative correlation between inclusive leadership and PSRB in male participants, and a positive but non-significant correlation in female participants. Conclusion: The findings suggest that inclusive leadership influences PSRB differently based on gender, with men showing a stronger negative association. This highlights the need to consider gender when studying leadership styles and their impact on workplace behavior. Novelty/Originality of this Study: This study contributes to the literature by examining the role of gender in the relationship between inclusive leadership and PSRB, offering insights into how inclusive leadership can differently affect men and women in the workplace.